A "Crisis" in the Making: The Correspondence of Hans Baron and Paul Oskar Kristeller. Issue 3 (2nd April 2016) - Rubini, Rocco
Abstract: This article summarizes and contextualizes the vast unpublished correspondence between Hans Baron (1900–1988) and Paul Oskar Kristeller (1905–1999), two of the most prominent twentieth-century scholars of Renaissance Humanism. It details how Baron and Kristeller came to take their first steps in Renaissance scholarship in Germany before political circumstances forced them into exile; it recounts the story of their emigration and their strategies for survival in Italy, Britain, and the United States; it reveals the impact of the American academy on their intellectual journeys and the extent to which they self-consciously stood for a methodology on the verge of extinction. Most important, the correspondence provides us with a personal etiology of the rebirth of Renaissance studies in the postwar period and of the concrete genesis of some of the books that brought it about.